THE EFFECT OF FINANCIAL AND NON-FINANCIAL VARIABLES ON STOCK UNDERPRICING IN THE SERVICE COMPANIES WHEN INITIAL PUBLIC OFFERING (IPO) IN INDONESIA STOCK EXCHANGE (BEI): A CASE STUDY IN SHARIAH AND NON-SHARIAH STOCKS FOR 2012-2017 PERIOD - Vabila Ananta Setya; Bayu Arie Fianto (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to investigate the factors that influence the underpricing of stocks in service companies during an initial public offering (IPO) on Bursa Efek Indonesia (BEI) for the period 2012-2017 (Comparison of Sharia and non-sharia stocks). The data used in this study consist of 20 stocks that experienced the underpricing from a total of 44 IPOs of sharia-compliant service companies and 19 stocks that experienced the underpricing from a total of 32 IPOs of non-shariah-compliant service companies. The research approach used is a quantitative approach with multiple linear regression analysis techniques. This research reveals that the underwriter reputation and auditor reputation have a significant effect on the underpricing at the IPO on Bursa Efek Indonesia (BEI) for the period 2012-2017.Keyword: Underpricing, Underwriter Reputation, Auditor Reputation, Financial Leverage, Return on Assets, Initial Public Offering (IPO)REFFERENCE Anwar, Y. (2010). Pasar modal sebagai sarana pembiayaan dan investasi. Bandung: Alumni.Beatty, R. P., & Ritter, J. R. (1986). Investment banking, reputation, and the underpricing of initial public offerings. Financial Economics, 15(1), 213–232.Carter, R., & Manaster, S. (1990). American finance association initial public offerings and underwriter reputation author (s): Richard Carter and Steven Manaster. The Journal of Finance, 45(4). 1045-1067.Chastina, Y., & Martani, D. (2005). Variabel-variabel yang Memperngaruhi Underpricing pada penawaran saham perdana di BEJ Tahun 1994-2001. SNA, 8.Daljono. (2000). Analisis faktor-faktor yang mempengaruho initial return saham yang listing di BEJ tahun 1990-1997. SNA, 3.Fahmi, I. (2012). Pengantar pasar modal panduan bagi para akademis dan praktisi bsinis dalam memahami pasar modal Indonesia. Bandung: Alfabeta CV.Ghozali, I., & Mansur, M. al. (2002). Analisis faktor-faktor yang mempengaruhi tingkat underpricing di bursa efek Indonesia. Bisnis dan Akuntansi, 4(1).Handayani, S. R. (2008). Analisis faktor-faktor yang mempengaruhi underpricing saham pada penawaran umum perdana (Studi kasus pada perusahaan keuangan yang Go Public di Bursa Efek Jakarta Tahun 2000-2006). Skripsi tidak diterbitkan. Semarang: Universitas Diponegoro.Hapsari, V. A. (2012). Analisis faktor-faktor yang mempengaruhi underpricing saham pada penawaran umum perdana di BEI Periode 20082010. Diponegoro Journal of Management, 1(1), 1–9.Jannah, K. M. (2016). Peluang investasi di pasar modal syariah.Kadek, P., Raditya, A., & Yasa, G. W. (2017). Reputasi auditor sebagai pemoderasi pengaruh informasi keuangan dalam prospektus pada tingkat underpricing penawaran saham perdana. E-Jurnal Akuntansi, 21(3), 1963-1992.Kasmir. (2010). Pengantar manajemen keuangan. Jakarta: Kencana Prenada Media Group.Khan, T., & Ahmed, H. (2008). Manajemen risiko: Lembaga keuangan syariah. Jakarta: PT Bumi Aksara.Kristiantari, I. D. (2013). Analisis faktor- faktor yang mempengaruhi underpricing saham pada penawaran saham perdana di Bursa Efek Indonesia. Ilmiah Akuntansi Dan Humanika, 2(2), 785-811.Lestari, A. H., Hidayat, R. H., & Sulasmiyati, S. (2015). Analisis faktor-faktor yang mempengaruhi underpricing saham pada penawaran umun perdana di BEI periode 2012-2014 (Studi pada perusahaan yang Melaksanakan IPO di Bursa Efek Indonesia periode 2012-2014). Administrasi Bisnis, 25(1), 1-9.Lestari, Y. O. (2011). Pengaruh informasi keuangan dan non keuangan terhadap return saham di pasar perdana. Akuntansi Aktual, 1(1), 1–10.Muhamad, S. (2006). Pasar modal dan manajemen portofolio. Surabaya: Erlangga.Nugroho, R., & Nanda, R. (2016). Analisis investasi atau penanaman modal dalam konsep ekonomi Islam. Universitas Islam Indonesia Yogyakarta.Retnowati, E. (2013). Penyebab underpricing pada penawaran saham perdana di Indonesia. Accounting Anlysis Journal, 1(4), 173–192.Safithri, M., Setyaningsih, I., Tarman, K., Suptijah, P., & Yuhendri, V. M. (2018). Potensi kolagen teripang emas sebagai inhibitor tirosinase. JPHPI, 21(2), 295-303.Siamat, D. (2005). Manajemen lembaga keuangan, kebijakan moneter dan perbankan. edisi pertama. Jakarta: Fakultas Ekonomi Universittas Indonesia.Sugiyono. (2014). Metode penelitian kuantitatif, kualitatif, dan R&D. Bandung: Alfabeta CV.Suyatmi, & Sujadi. (2006). Faktor-faktor yang mempengaruhi underpricing pada penawaran umum perdana di Bursa Efek Jakarta. Jurnal Benefit, 10(1), 11–32.